Gert-model of processes of active analysis of the system resource management and implementation in the computer system - Lysytsia, D. O.; Semenov, S. G.; Lysytsia, A. O. (Education and Science, Praha, 2018)
One of the main and complex stages of the algorithm allocation process from binary code is presented - optimization stage. The main feature of the developed method is the adaptation to the requirements of the task of allocating a set of attractors with common features. Furthermore, the use of optimization algorithm, which eliminates unnecessary loads and unloads, will significantly reduce the complexity of the developed graph.
Keywords: binary code; optimization; allocation of algorithm